War reparations and the UN Compensation Commission : designing compensation after conflict - Gibson, Christopher S.; Rajah, Trevor M.; Feighery, Timothy John, 1962- (New York : Oxford University Press, 2015)
The United Nations Compensation Commission (UNCC) is a claims reparation programme created by the United Nations Security Council in May 1991, after the UN-authorised Allied Coalition Forces' military operations terminated the seven-month invasion and occupation of Kuwait by Iraq and liberated Kuwait. This text is a collective work on the UNCC claims programme by experts who have contributed to its progress, and who have assisted in paving the way for more informed research on the Commission and its jurisprudence.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 24, 2015).
Keywords: Persian Gulf War, 1991 -- Claims; United States -- Claims vs. Iraq; Iraq-Kuwait Crisis, 1990-1991 -- Claims; Kuwait -- Claims vs. Iraq; United Nations Compensation Commission; Liability for environmental damages -- Persian Gulf Region; Government liability (International law); Compensation (Law)